PENGARUH INTENSITAS PENGGUNAAN MEDIA SOSIAL, KECEMASAN SOSIAL, DAN PERCAYA DIRI TERHADAP PERILAKU KEUANGAN MELALUI TAKUT KETINGGALAN SEBAGAI VARIABEL PERANTARA - Angeline Fiona; Oen Eric Harianto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The rapid development of social media has had a significant impact on the financial behavior of the younger generation. University students are one of the groups most vulnerable to digital influences, including increased social anxiety, decreased self-esteem, and the phenomenon of Fear of Missing Out (FoMO) that triggers consumptive behavior. This study aims to analyze the effect of social media usage intensity, social anxiety, and self-esteem on the financial behavior of students and to test the role of FoMO as a moderating variable. This research uses an explanatory quantitative method with Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis. The study sample consisted of 227 active social media users from Ciputra University, obtained through random sampling. The research results are expected to contribute empirically to the development of literature on financial behavior based on digital psychology, as well as provide recommendations for educational and financial institutions to improve financial literacy and reduce the negative impact of FoMO among students. This study also provides a foundation for developing a digital psychology-based intervention model to promote healthier financial behaviors.